2017
DOI: 10.1016/j.adolescence.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent social media use and mental health from adolescent and parent perspectives

Abstract: This study investigated adolescent and parent reports of adolescent social media use and its relation to adolescent psychosocial adjustment. The sample consisted of 226 participants (113 parent-adolescent dyads) from throughout the United States, with adolescents (55 males, 51 females, 7 unreported) ranging from ages 14 to 17. Parent and adolescent reports of the number of adolescents' social media accounts were moderately correlated with parent-reported DSM-5 symptoms of inattention, hyperactivity/impulsivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
249
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(285 citation statements)
references
References 22 publications
20
249
1
15
Order By: Relevance
“…There has also been increasing attention on the negative outcomes associated with social media in adolescence (Best et al 2014;Strasburger et al 2013;Woods and Scott 2016), with some indication that the mental health of girls may be vulnerable to its use (Booker et al 2018). Although a moderate significant association have been found between social media and depressive symptoms in young people, most of these studies are crosssectional or of a limited duration (Barry et al 2017;McCrae et al 2017). There is recent evidence that increasing use of social media is associated with increasing depressive symptoms in girls (Raudsepp and Kais 2019).…”
Section: Early Predictors and Adolescent Outcomesmentioning
confidence: 99%
“…There has also been increasing attention on the negative outcomes associated with social media in adolescence (Best et al 2014;Strasburger et al 2013;Woods and Scott 2016), with some indication that the mental health of girls may be vulnerable to its use (Booker et al 2018). Although a moderate significant association have been found between social media and depressive symptoms in young people, most of these studies are crosssectional or of a limited duration (Barry et al 2017;McCrae et al 2017). There is recent evidence that increasing use of social media is associated with increasing depressive symptoms in girls (Raudsepp and Kais 2019).…”
Section: Early Predictors and Adolescent Outcomesmentioning
confidence: 99%
“…Being a poor substitute, the former leads to the further weakening of intimate social bonds and an accompanying intensification of insecurity. Indeed, many commentators prefer the term, "antisocial media" (Woods 2016)-a reflection of its potentially toxic role in social relations and its contribution to the current crisis in young people's mental health (Barry et al 2017; Royal Society for Public Health 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Several recent studies have also found negative associations of social media use with a variety of indicators of mental health among adolescents and young adults. For example, in a study drawing data from a sample of adolescents and their parents throughout the United States, Barry, Sidoti, Briggs, Reiter, and Lindsey (2017) found that social media use is moderately and positively related to adolescent-reported fear of missing out and loneliness as well as with parent-reported hyperactivity/ impulsivity, anxiety, and depression. Similarly, in a national survey of U.S. young adults, Primack et al (2017) found that compared with individuals who use 0 to 2 social media platforms, individuals who use 7 to 11 social media platforms have substantially higher odds of having increased levels of depression and anxiety symptoms.…”
mentioning
confidence: 99%